Identification of Flavor Compounds from Soybean Peel Flour (Glycine max L. Merr) with the Addition of Kaffir Lime Leaves in the Blanching Process - Nurul, Adinda; Jariyah, Jariyah (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Soybean husk flour is flour made from the main ingredient of soybean husk which undergoes a flouring process so that it can be substituted in making bakery products such as brownies, bread and cookies. Apart from having a fairly high nutritional content, soybean epidermis also has a unpleasant odor that consumers don't like, so it needs to be reduced, one way is by blanching and adding kaffir lime leaves. This research aims to find the best treatment for the length of time for blanching and adding kaffir lime leaves. This research used a Completely Randomized Design (CRD) with two factors and two replications. Factor I is the length of blanching time (10 and 20 minutes) and factor II is the amount of added kaffir lime leaves (0, 5, 10, 15 and 20 gr). The data obtained was then analyzed using ANOVA and continued with the Duncan Multiple Range Test (DMRT) at the 5% level. The best treatment results were obtained in the treatment with a long blanching time of 20 minutes with the addition of 20 grams of kaffir lime leaves with characteristics of 9.55% water content, 1.98% ash, 7.77% protein, 1.60% fat, 30.02% crude fiber and flavor compounds found, among others. pentanal, oxirane,2-(1,1-dimethylethyl)-3-ethyl-, cis-, hexanal, furan, 2-pentyl-5-, octen-1-ol, (Z)-1,1-, dodecanediol, diacetate and cedrene.